2020
DOI: 10.1080/24750263.2020.1741705
|View full text |Cite
|
Sign up to set email alerts
|

EarthwormDrawida(Moniligastridae) Molecular phylogeny and diversity in Far East Russia and Northeast China

Abstract: In the Sikhote-Alin and Changbai Mountains of the Amur River region, earthworms of genus Drawida inhabit the northern boundary of their natural habitat. They are represented by the epigeic and anecic life-forms, three steady colour morphs and eight valid species, yet the genetic lineages of 11 have yet to be described. Based on mt-COI gene fragment sequence data, epigeic and anecic earthworms are shown to differ from one another at the interspecific level. Polymorphism and genetic intraspecific diversity are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The average interspecific distance in the genus Drawida was previously reported as 22%, and the maximum one was 34.3% between D. impertusa and D. deshayesi ( Thakur et al 2021 ). The p -genetic distance was also known to range from 18% between D. koreana and D. japonica japonica to 24.82% between D. koreana and D. gracilis ( Zhang et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average interspecific distance in the genus Drawida was previously reported as 22%, and the maximum one was 34.3% between D. impertusa and D. deshayesi ( Thakur et al 2021 ). The p -genetic distance was also known to range from 18% between D. koreana and D. japonica japonica to 24.82% between D. koreana and D. gracilis ( Zhang et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…India, Myanmar, Malay Peninsula, Thailand, Cambodia, Laos, Vietnam, China, Korea, Japan, Philippines, Malaysia, Indonesia, Borneo, Sumatra, Java, Sri Lanka, Taiwan, Far East of Russia, Caribbean, Australia, and various Pacific islands ( Gates 1972 ; Blakemore 2002 ; Chang et al 2009 ; Zhang et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only eight species are classified as Metaphire, 3 to Amynthas, and one as unidentified Fig. 3 Divergence time estimation from phylogenetic tree inferred from partial COI gene sequences of 59 pheretimoid species and H. medicinalis as an out-group using calibration points 52) . The divergence values are given at the nodes of the phylogeny in Million years (Ma) .…”
Section: Discussionmentioning
confidence: 99%
“…Earthworms inhabiting meadows and swamps are epi-endogeic, black-colored and have an optional diapause; forest earthworms are anecic, have a brownish color and an obligate diapause (Ganin, 2013(Ganin, a, 2013Ganin, 2014). However, upon further study of the identified forms, especially the study of their phylogeny using molecular biology methods, it was found that forest anecic earthworms Drawida ghilarovi consist of ten separate genetic lineages, which hypothetically can be different species, whereas the black epi-endogeic meadow and swamp morph represents a new species (Zhang et al, 2020).…”
Section: Polymorphism and Molecular-biological Studies Of Earthworms ...mentioning
confidence: 99%